External oscillator‐less TDC‐based all‐digital temperature sensor. Issue 5 (28th February 2019) - Shimada, Hideto; Mizuno, Kentaro
Abstract: This paper presents a Time‐to‐Digital Converter (TDC)‐based all‐digital temperature sensor with small inaccuracy even at wide temperature range. The proposed sensor utilized CMOS inverters show different temperature characteristics to embed an oscillator that previous sensors have used as external component. Moreover, the temperature characteristic of a diode is used to improve the temperature inaccuracy. The sensor in 180‐nm CMOS process tested from −40°C to 200°C shows −2.56°C to +2.84°C inaccuracy.